Scientific and investigative skills through formative research in secondary school students - Ruiz Pérez, Aurelio (2014)
This research arises from the observation of an easily observable deficiency the development of scientific-investigative skills in students from first to fifth degree of Secondary Education. Overcoming was achieved with the development of various types of research, previously thought according to the authors of the bibliographic sources and counting with the endorsement of professors of the E. I. Inca Garcilaso de la Vega of the district of Morrope. Province and Region of Lambayeque. Students were previously trained, then they focused on the research with the tutoring to a university student connoisseur of the research and who wants to gain more experience. In the end it was elaborated, presented, supported and approved a report, a monograph, a life story, an essay and a dissertation according to the degree of studies, thus it was possible to develop scientific and research skills not formerly known by the students. The emerging product stands out related to the elaboration and presentation of the autobiography by the students themselves, as well as the enjoyment of the children’s game, fundamentally of students.